2006
DOI: 10.1037/0022-0167.53.2.241
|View full text |Cite
|
Sign up to set email alerts
|

The Colonial Mentality Scale (CMS) for Filipino Americans: Scale construction and psychological implications.

Abstract: Colonial mentality, or internalized colonialism, has been discussed by scholars and by Filipino American community members as a significant factor in the experiences of contemporary Filipino Americans, yet this construct has not received empirical attention in psychology. The authors of the current study addressed this gap in the Asian American psychological literature by developing the Colonial Mentality Scale for Filipino Americans, a theoretically derived and psychometrically tested multidimensional measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
268
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(297 citation statements)
references
References 36 publications
21
268
2
6
Order By: Relevance
“…Another description of Filipino values found in the literature was the prevalence of the neo-colonized mentality that many Filipinos came to adopt (Bergano & Bergano-Kinney, 1997;David & Okazaki, 2006;David, 2008;Julag-ay, 1997). This was best depicted by one of the women who expressed her wish to have a "Caucasian boyfriend" since she was a young girl.…”
Section: Discussionmentioning
confidence: 99%
“…Another description of Filipino values found in the literature was the prevalence of the neo-colonized mentality that many Filipinos came to adopt (Bergano & Bergano-Kinney, 1997;David & Okazaki, 2006;David, 2008;Julag-ay, 1997). This was best depicted by one of the women who expressed her wish to have a "Caucasian boyfriend" since she was a young girl.…”
Section: Discussionmentioning
confidence: 99%
“…The ideas of these scholars served as the foundation for David's (2011) conceptualisation of colonial mentality (David & Okazaki, 2006). David's research indicated that colonial mentality is experienced by Filipino Americans, and is characterised by a perception of cultural inferiority.…”
Section: Colonial Debtmentioning
confidence: 99%
“…David's research indicated that colonial mentality is experienced by Filipino Americans, and is characterised by a perception of cultural inferiority. One subcomponent of colonial mentality is colonial debt (David, 2011;David & Okazaki, 2006). Colonial debt refers to an internalised acceptance and tolerance of oppression that colonised individuals hold toward their colonisers.…”
Section: Colonial Debtmentioning
confidence: 99%
See 2 more Smart Citations